Designing Educational Tourist Routes in Almaty (Journal of Educational Sciences, 2018)
The educational tourist route is a geographical way of people’s movement, which determines a sequential visit to historical pedagogical places of interest and educational institutions. The peculiarity of the educational and tourist route is the emphasis on didactic goals and tasks of providing the tourist with knowledge in the history of pedagogy and education, modern development of pedagogy. The aim of the research is the development of an educational tourist route for introduction into the history of pedagogy and education in Almaty. Materials and methods of research. The definitions of the concepts "educational tourism” and “educational tourist route” were given based on the analysis of the scientific literature. A model for the development of educational tourism for the city of Almaty and the republic has been developed. Systemic, tourist, logistical, pedagogical, androgogic, interdisciplinary approaches were used. Educational tourist routes of Almaty city are developed by the projecting method. The educational tourist route includes the following items: the museum of the first Minister of Education A. Baytursynov, a former orphanage for the city of Verny, a former men’s gymnasium, a former city training college. The route runs along the streets of Baytursynov, Kabanbai batyr, Bogenbai batyr, Pushkin, Tole bi, Kaldayakov, Gogol. The length of the route is about 4.2 km. The planned time for walking (without visiting the museum’s expositions) is about 60 minutes.Key words: educational tourist route, educational tourism, history of education, patriotism, leisure,cognitive process.